Fibroblast Response to Cyclo- and Organic Phosphate Solutions: A Cytotoxicity Study - de Morais, Leonardo Antônio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Sampaio, Caio [UNESP]; de Aguiar, Vitória Bittencourt [UNESP]; Guisso, Luigi Pedrini [UNESP]; Ferraresso, Lucas Fernando Oliveira Tomáz [UNESP]; Pessan, Juliano Pelim [UNESP]; Hosida, Thayse Yumi [UNESP] (MDPI, 2025)
Although the anticaries properties of phosphate-based compounds have been extensively investigated in recent years, their potential cytotoxic effects remain underexplored. This study evaluated the cytotoxicity of solutions containing sodium trimetaphosphate (TMP), sodium hexametaphosphate (HMP), or calcium glycerophosphate (CaGP). NIH/3T3 fibroblasts were cultured in Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum and maintained at 37 °C, 100% humidity, and 5% CO2. The cells were seeded in 96-well plates at a density of 104 cells per well and incubated for 24 h. Subsequently, different dilutions of 10% TMP, HMP, or CaGP solutions were applied to the cells. Cell viability was assessed at 24/48 h using the MTT assay. The data were subjected to two-way ANOVA and Fisher’s LSD test. Spearman’s rank correlation was performed. HMP dilutions led to significantly lower cell viability compared to the other compounds, regardless of the incubation period. TMP maintained higher cell viability from 1/8 dilution onwards, regardless of the incubation time. For CaGP, an increase in cell viability was observed at 1/8 dilution after 24 h. In conclusion, TMP and CaGP demonstrated reduced cytotoxicity at higher dilutions compared to HMP, suggesting their potential as promising candidates for the development of novel biomaterials.